The Acceptance and the Development of Renal Function of People with Diabetes Mellitus - Isroin, Laily (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Chronic renal failure (CRF) is a silent killer disease. CRF disease is mainly caused by diabetes mellitus and hypertension.Patients with diabetes mellitus should be able to accept the disease so that it can control blood sugar and blood pressure. Sectional analytic study design to measure self-management that includes cognitive, self-efficacy, psychological, social and environmental patients which associated with decreased renal function, blood pressure and blood sugar. The study was conducted in dr. HarjonoHospital Ponorogo with a sample of patients with hypertension and diabetes mellitus outpatient. Total sample of 42 patients with diabetes mellitus were taken by purposive. Analysis using chi square test and the magnitude of the risk factors using OR. There was a significant correlation between the level of acceptance of the disease with glomerular filtration rate (GFR) and receiving negative disease risk 4 times the decline in GFR compared with positive reception disease. Patients with diabetes mellitus who can not control blood sugar normal it will be at risk of decreased GFR was 2.07 times compared with patients whose blood sugar normal and stable. Patients with diabetes mellitus GFR decreased by 3 to 5 degrees of 64.3%.The decline in GFR at level 5 hemodialysis patients require lifelong therapy. This will reduce the productivity of patients and social and economic burden to both family and government.